Enabling models of Internet eXchange Points for developing contexts. (2020) - Ó Briain, Diarmuid; Denieffe, David; Okello, Dorothy; Kavanagh, Yvonne
Abstract: In 2009, fibre-optic cables landed on the East coast of Africa, the last major area of the world to be connected to the Internet triggering a decade of Internet development (Graham et al., 2015). During the same period, there has been a general transformation of the Internet from static content to video streaming. Technologies such as Software Defined Networking (SDN) and Network Functions Virtualisation (NFV) are about to reshape the Internet once again. Globally Internet eXchange Points (IXP) have been a key node on the Internet and a central location for Content Delivery Networks (CDN), though in East Africa they have generally been confined to large cities. There is an understanding that if technology hubs are to develop in other cities, the Internet ecosystem, including IXPs, must extend outwards. This research uses a Proof of Concept (PoC) system design methodology to investigate solutions that containerise IXP functions and develops affordable models for IXPs of various sizes and configurations based on both traditional and software-defined switching paradigms as well as automate the IXP build function. The research argues that it is necessary to develop a national IXP ecosystem by supplementing the national IXP with local IXPs to support economic development outside of the major economic cities of the region. The technology solutions must be used in conjunction with research on the political economy landscape plus optimum deployment to ensure success. This research demonstrates that systems can be designed which are achievable and affordable by exploiting the most suitable model and switching technology for each site. It also determines that software-defined models offer the potential for application development across the IXP. This research concludes that with a combination of function containerisation and astute model selection it is possible to build an affordable set of IXPs to support multiple technology hubs across a national Internet ecosystem. Proposed systems are discussed in the context of East Africa and testbed results discussed in relation to the optimum system design which can be deployed in any IXP setting.